Bus Scheduling as a Graph Coloring Problem - Stanislav Paluch (Communications - Scientific letters of the University of Zilina, 2003)
The fundamental vehicle-scheduling problem (VSP) is usually formulated as a matching problem for which there exists a polynomial algorithm. The formulation of VSP as a graph coloring problem may seem not to be practical since a graph coloring problem is NP-hard and it is not a good idea to solve a polynomial problem using a non polynomial algorithm. However, no polynomial algorithms have been found for generalizations of VSP and hence the graph coloring formulation offers good approximation algorithms for their solution.